1994
DOI: 10.1063/1.112988
|View full text |Cite
|
Sign up to set email alerts
|

Topmost surface analysis of SrTiO3 (001) by coaxial impact-collision ion scattering spectroscopy

Abstract: The terminating atomic plane of SrTiO3 (001) surface was investigated by means of coaxial impact-collision ion scattering spectroscopy (CAICISS). CAICISS spectra proved that SrTiO3 (001) surfaces of as-supplied substrates as well as of O2-annealed substrates were predominantly terminated with TiO2 atomic plane, while the SrO atomic plane came at the topmost surface of SrTiO3 (001) homoepitaxial film. This indicates the structural conversion of the topmost atomic layer from TiO2 to SrO occurred during the SrTiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…16 In this case, the weakest bond links precisely the BaO plane to the CuO plane. To correlate a measured property with a specific stack requires two important steps: ͑i͒ to prepare a substrate with a unique and known TL contrary to the observed mixture [17][18][19][20] and ͑ii͒ to identify the TL of the dominant stack on the film surface. Critical to both steps is a direct procedure to check on a local scale the presence, distribution, and nature of the different TL.…”
mentioning
confidence: 99%
“…16 In this case, the weakest bond links precisely the BaO plane to the CuO plane. To correlate a measured property with a specific stack requires two important steps: ͑i͒ to prepare a substrate with a unique and known TL contrary to the observed mixture [17][18][19][20] and ͑ii͒ to identify the TL of the dominant stack on the film surface. Critical to both steps is a direct procedure to check on a local scale the presence, distribution, and nature of the different TL.…”
mentioning
confidence: 99%
“…A large number of studies have been performed in recent years to understand and to determine a variety of SrTiO 3 surface structures realized under different experimental conditions. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Some of the reported experimental observations are summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen vacancy concentration is neither high enough to produce conductivity nor to produce a surface reconstruction. It is worth mentioning that shell model calculation [15] and STM [11][12][13][14] works have shown that the (100) SrTiO 3 surface is Ti-Oterminated. The same pattern was detected up to 740°C (see Fig.…”
Section: Leed Resultsmentioning
confidence: 99%